2021
DOI: 10.1029/2020ef001734
|View full text |Cite
|
Sign up to set email alerts
|

Will Individual Actions Do the Trick? Comparing Climate Change Mitigation Through Geoengineering Versus Reduced Vehicle Emissions

Abstract: Global temperatures have risen by about 1.1°C from pre-industrial levels, largely due to carbon dioxide (CO 2) emissions from human activities (Ritchie & Roser, 2017). With already-implemented climate policies remaining as they are, this increase could reach as high as 3.7°C by 2100 (Ritchie & Roser, 2017), well above the goal of keeping post-industrial warming within 1.5°C (IPCC, 2018). To comply with this goal, global emissions need to be net-zero by approximately 2050 (IPCC, 2018), adding to the sense of ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Also, car sharing and demand management are suggested [ 126 , 127 ]. Other research has found that the highest reduction potential, in terms of private consumption habits, is flying less and using an electric vehicle (or living car-free) [ 40 , 128 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, car sharing and demand management are suggested [ 126 , 127 ]. Other research has found that the highest reduction potential, in terms of private consumption habits, is flying less and using an electric vehicle (or living car-free) [ 40 , 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…Much like carbon capture and storage solutions, geoengineering technologies are post-emission solutions [ 297 ], and thus may do little to actually curb GHG emissions and alter policies and consumption behavior. Geoengineering may in fact encourage complacency and reduce motivation for individual action such as using ‘climate-friendly’ modes of transport, reducing air travel, reducing meat consumption, and reducing electricity use [ 128 ]. Thus, while some geoengineering techniques may become viable in the future, significant GHG emissions reductions are still where most effort needs to be applied [ 298 ].…”
Section: Resultsmentioning
confidence: 99%